DIALOGICAL RELATIONS IN THE EROTIC TALE CINCO SENTIDOS, BY MANOEL LOBATO - Pernambuco, Juscelino; Pugina, Rosana Leticia [UNESP] (Univ Estado Mato Grosso, 2018)
The objective of this paper is to analyze the dialogical relations in an erotic tale and understand the different discursive constitutive positions in a narrative plot. The analysis will be based in the Bakhitinian concepts of dialogism (1987; 1997; 1998; 2006) and in studies of researchers of his writings. Related to eroticism, it will be used Almeida's (1980), Bataille's (1980), Castelo Branco's (1984), Durigan's (1985) Moraes and Lapeiz's (1986), Paz's (1993) studies, among others. It's intended to prove with this article that the high quality erotic literature has a significative potential to show natural human being behaviors in the happening of the existence.
Keywords: Bakhtin; Dialogical relations; Brazilian erotic tale; Cinco sentidos